Elastic Abdominal Binders Attenuate Orthostatic Hypotension in Parkinson's Disease. Issue 2 (27th November 2015) - Fanciulli, Alessandra; Goebel, Georg; Metzler, Bernhard; Sprenger, Fabienne; Poewe, Werner; Wenning, Gregor K.; Seppi, Klaus
Abstract: Background and Methods: To investigate the possible efficacy of an elastic abdominal binder to control orthostatic hypotension (OH) associated with Parkinson's disease (PD), 15 patients with PD and OH were enrolled in a single‐blind crossover study with elastic abdominal versus placebo binder on two different days, separated by a 1‐day interval, followed by a 4‐week open‐label follow‐up. Results: Intervention significantly reduced blood pressure fall upon tilting. The mean difference (standard deviation; 95% confidence intervals) between abdominal binder versus placebo was +10 mm Hg (10.2; +3.5, +16.5; P = 0.006). No significant effect on supine mean blood pressure values was observed compared to placebo ( P = 0.3). Symptoms of OH decreased significantly during follow‐up ( P = 0.003), as assessed by means of the Orthostatic Hypotension Questionnaire. Conclusions: Our findings suggest that elastic abdominal binders may be a simple complementary tool to alleviate OH in PD.